A New "F-Lueg" Cryptosystem and its Security - Choo, Mun Yoong (2002)
In this thesis, we present a new public-key cryptosystem and a new digital signature based on the extended Lucas function analogue to EIGamal cryptosystem. We name it" F-LUEG" cryptosystem. Chapter 2, we point out how an extended Lucas function can be used in a cryptosystem, which has been presented Md Said in his thesis [Rus]. This extended Lucas function is an extension from Lucas function. In chapter 3, we provide some explanation about EIGamal cryptosystem, which has been presented by TEl Gamal in 1985. Finally, from these two cryptosystems, this thesis associate the extended Lucas and EIGamal cryptosystems to develop a new cryptosystem, which is the F-LUEG cryptosystem.